A Conceptual Framework to use Remediation of Errors Based on Multiple External Remediation Applied to Learning Objects - Maici Duarte Leite; Diego Marczal; Andrey Ricardo Pimentel; Alexandre Ibrahim Direne (OmniaScience, 2014)
This paper presents the application of some concepts of Intelligent Tutoring Systems (ITS) to elaborate a conceptual framework that uses the remediation of errors with Multiple External Representations (MERs) in Learning Objects (LO). To this is demonstrated a development of LO for teaching the Pythagorean Theorem through this framework. This study explored the remediation process of error by a classification of error in mathematical, providing support for the use of MERs with the remediation of error. The main objective of the proposed framework is to assist the individual learner in the recovery of a mistake made during the interaction with the LO, either through carelessness or lack of knowledge. Initially, we present the compilation of the classification of mathematical errors and their relationship with MERs. Later the concepts involved with conceptual framework proposed. Finally, an experiment with LO developed with a authoring tool called FARMA, using the conceptual framework for teaching the Pythagorean Theorem is presented.